Arquitetura das escolas públicas nas reformas educacionais mineiras (1982-1930) - Claudio Lucio Fonseca (2004)
This dissertation deals with the architecture found in the public elementary schools in Belo Horizonte, projected and/or constructed in accordance with educational reforms of the state of Minas Gerais inplanted during the period beginning in 1892, when the Afonso Pena Reform was created, until 1930, the last year in which Antonio Carlos was the governor of Minas Gerais, during which the Francisco Campos reform was instituted. This is based on architectural blueprints, photographs, official documents and documents of the schools themselves, besides newspapers articles, this paper analyses, identifies and characterizes these schools, as places as well as political, social and ideological representations as seen through their architecture. Comparing the schools built during Antonio Carlos term as governor with those built during previous administrations, the dissertation studies the first ones as to formed and preserved recollection and also as propaganda instruments of those administrations in reference to education. The schools were places where headmasters and teachers were intensely involved, both professionally and emotionally. For the students, if eventually the schools became places of leisure and recreation, they were also places of discipline. Architecturally there was more continuity than interruption. The principal change could be seen in the fronts of the buildings as the continuity could be observed in the blueprints, which, although there were teaching innovations, basically kept the same features as the blueprints from 1910.